PROGRAMMING AS ONE OF THE MAIN APPROACHES IN THE DEVELOPMENT OF CHILDREN’S COMPUTATIONAL THINKING - Ikromova, Musharraf (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective. Digital technologies are developing so quickly that sometimes you don't even have time to grasp the essence of these technologies. Some "lighthouse" companies are rapidly introducing cyber-physical systems and artificial intelligence into their production in order to maintain their place on the world stage. In such a world, specialists are now needed who not only actively use these technologies, but also develop them. And how to prepare the growing generation for such a world where the integration of various scientific disciplines and discoveries is proceeding at a rapid pace, and where professions disappear en masse and new ones appear, which to a large extent require programming skills. All over the world they are discussing what skills and competencies we should equip the younger generation so that in the future they can calmly rule the world. Computational thinking is recognized as a necessary competence and skill set for the 21st century. Research shows that programming is one of the approaches to shaping and developing the computational thinking of adults and children. Methods. Today they are trying to teach programming at all levels of the education system, starting with preschool. Two approaches are known, teaching basic programming skills, constructionism and fundamentalization of programming, and two strategies of unplugged and connected classes. Results. The analysis of the tools used in the development of computer thinking of young children is made and is given in the form of a column. Conclusion. The strategy unplugged is more suitable for the development of computer thinking in our country